Solvent Extraction of Molybdenum (Vi) from Aqueous Solution Using Ionic Liquids as Diluents - Romero-Figueroa, J; Quijada-Maldonado, E; Torres-Saldias, M (Elsevier B.V., 2017)
This work deals with the recovery of Molybdenum (VI) (Mo) from aqueous solutions carried out by solvent extraction (SX) using the bis(2-ethylhexyl) phosphoric acid (D2EHPA) diluted in kerosene and compared with two hydrophobic room temperature ionic liquids (RTILs) as potential replacements of the kerosene. These RTILs were 1-butyl-3-methyl-imidazolium bis (trifluoromethylsulfonyl) imide, [bmim][Tf2N], and 1-octyl-3-methyl-imidazolium bis(trifluoromethylsulfonyl)imide [omim][Tf2N], because of its excellent properties such as negligible vapor pressure, high hydrophobicity and better extraction capacity than conventional organic diluents. Experimental results indicate that the extraction stoichiometry agrees with a cation exchange with formation of a neutral complex. The use of the selected RTILs as diluents involves higher extraction percentages for the whole measured range of extractant concentration and aqueous-organic ratios, reducing four times the required volume of diluent compared to the experiments carried out with kerosene. Furthermore, the proposed extraction medium offers excellent stripping capacity when a solution of ammonium carbonate is used as a stripping phase. © 2016 Elsevier B.V.
Keywords: Molybdenum; Solvent extraction; Ionic liquids